FROM POLITICAL TO CULTURAL: THE TRANSFORMATION OF SPATIAL VALUES IN THE KEPATIHAN AREA OF SURAKARTA: From Politic to Cultural: Transformation of Spatial Values in Kepatihan Surakarta Area - Arnindya Afifah Urfan,; Sudaryono, Sudaryono (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2024)
One of the locations that had a great deal of urgency during the Surakarta Palace era is the Kepatihan district, where the Kepatihan Institution put the government system into place. This region was burned by the unrest that followed the incident with Indonesian independence in Surakarta. In addition to being a neighbourhood with offices and residences, this area was also referred to as a "arts pocket" because to the thriving arts scene there. This article investigated the transformation of the Kepatihan area's image from one that was primarily political to one that was cultural, using the phenomenological technique. The study's findings demonstrated that, despite the fact that the area's early designation was strongly tied to its political reputation, Patih Sosrodiningrat IV's establishment of the Paheman Radya Pustaka helped to shape the region's cultural identity. The Kepatihan area's current cultural image was portrayed by Paheman Radya Pustaka, and the community is still working to sustain it with the help of the local government.